Application of Analytic Hierarchy Process and Simple Additive Weighting in Designing The Best Employee Selection Decision Support System at PT Pos Indonesia - Karsim, Karsim; Dharmawan, Donny; Mus Abdul, Elfis; Zulaika, Siti; Mertua Agung Durya, Ngurah Pandji (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to compare the best employee evaluation outcomes using the analytical hierarchy process (AHP) technique and simple additive weighting (SAW) method as a support system for best employee suggestions. The author employed four different approaches for gathering data for this study: literature studies, interviews, observation, and similar literature studies. The RAD paradigm is being used in the development of this decision support system (DSS). The unified modeling language, or UML, tool is used in this system development methodology. It's time to put the system into action after it has been designed and analyzed. The black box testing methodology will be used for the experiments. Based on the research results, it was found that this system was able to assist decision makers in providing employee assessments quickly and precisely according to the predetermined time, whereas previously managers were always late and exceeded the time limit when assessing employees. The output of this system is that it can provide direct reports to the employees being assessed to find out the results of the scores obtained and make decisions about selecting the best employees. A decision support system for employee performance assessment uses the PHP and MySQL programming languages as the database. AHP and SAW methods, rapid application development (RAD) system development methods, and system testing with black box testing.